Inflasi Memoderasi Hubungan Capital Intensity, Firm Growth dan Exchange Rate dengan Firm Value Pada Perusahaan Sektor Energi yang Terdaftar dalam Bursa Malaysia Tahun 2019-2023 - Vicky Haeru Putera; Holiawati Holiawati; Zulfitra Zulfitra (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The purpose of this study is to examine and empirically demonstrate how inflation moderates the link between firm value, exchange rate, capital intensity, and company growth. This study employs an associative quantitative research design. The secondary data utilized was gathered from the www.bursamalaysia.com website. Companies in the energy sector that are listed on Bursa Malaysia between 2019 and 2023 make up the study's population. Purposive sampling using preset criteria was employed to carry out the sampling procedure, yielding 140 observations in total. Moderated regression analysis (MRA), and multiple linear regression techniques were used to test the data, hypothesis test (statistical t-test and coefficient of determination test) using the Eviews 12 program. The study's findings show that while business expansion and exchange rates have little bearing on firm value, capital intensity does. Capital intensity, firm growth, and the exchange rate with firm value cannot be moderated by inflation.